Factors associated with nursing students’ compliance with standard precautions: a self-reported survey - Moon, Kyoung ja; Hyeon, Yong Hwan; Lim, Kyung Hee (International Journal of Infection Control, 2019)
Adhering to standard precautions is a key factor in reducing the risk of infection among nurses and nursing students. This study identified nursing students’ compliance with standard precautions and the factors associated with their compliance. This descriptive survey included 176 nursing students from a regional nursing college. Compliance with standard precautions was assessed using a 20-item questionnaire. Data were analysed using t-tests, a one-way analysis of variance, and a multiple regression analysis. Participants’ overall compliance rate was 50.5%. Concerning general characteristics, significant differences were found regarding needle-stick or sharps injuries, practicum department (surgical and paediatric), and type of contact (faeces). Needle-stick or sharps injury experience (β = -0.225) and surgery practicum department (β = 0.182; Adj R² = 0.063; p = 0.001) had a significant effect on compliance level. Standard precautions should be emphasized in the nursing curricula, along with systematic continuing education. Educational programs for needle-stick or sharps injury prevention should also be included in standard precautions curricula.